Effects of rotation speed on microstructure and mechanical properties of non-prehole riveting process for high-strength aluminium alloys - Yunpeng Liu; Yunwu Ma; Ming Lou; Entao Zhou; Bowen Zhang; Zhilei Fan; Ende Ge; Huan Zhao; Yongbing Li (Materials & Design)
Traditional solid riveting and hi-lock bolt (HLB) are widely adopted in the aircraft assembly, but require pre-drilled holes before joining. In this research, an improved friction self-piercing riveting process was developed to connect 2.0 mm + 4.0 mm AA7075-T6 aluminium sheets without pilot holes. To clarify the impact of rivet rotation speed, the axial force, torque, geometric quality, microhardness and mechanical properties were experimentally investigated. With the rotation speed increasing from 1600 rpm to 5600 rpm, the maximum axial force minorly fluctuated around 10.5 kN but the maximum torque declined from 16.0 Nm to 6.0 Nm. The frictional heat input increased from 4000 J to 5100 J, resulting in a wider thermal softening zone and lower sheet microhardness. Crack, size reduction and void defects on aluminium threads were eliminated with the increment of rotation speed. One inner solid-state bonding zone was formed at rotation speeds smaller than 4600 rpm, but two inner solid-state bonding zones were generated at the rotation speed of 5600 rpm. The joint lap-shear strength was negatively affected, whilst the average peak load was always greater than 9.0 kN. The joint cross-tension strength was also affected but the average peak load was always greater than 4.0 kN.